Heart Rate and Muscle Oxygenation Kinetics During Dynamic Constant Load Intermittent Breath-Holds - Bouten, Janne; De Bock, Sander; Bourgois, Gil; de Jager, Sarah; Dumortier, Jasmien; Boone, Jan; Bourgois, Jan G. (Frontiers in Physiology, 2021)
Introduction: Acute apnea evokes bradycardia and peripheral vasoconstriction in order to conserve oxygen, which is more pronounced with face immersion. This response is contrary to the tachycardia and increased blood flow to muscle tissue related to the higher oxygen consumption during exercise. The aim of this study was to investigate cardiovascular and metabolic responses of dynamic dry apnea (DRA) and face immersed apnea (FIA). Methods. Ten female volunteers (17.1 ± 0.6 years old) naive to breath-hold related sports, performed a series of 7 dynamic 30 second breath-holds while cycling at 25% of their peak power output. This was performed in two separate conditions in a randomized order: FIA (15°C) and DRA. Heart rate and muscle tissue oxygenation through near-infrared spectroscopy were continuously measured to determine oxygenated (m[O2Hb]) and deoxygenated hemoglobin concentration (m[HHb]) and tissue oxygenation index (mTOI). Capillary blood lactate was measured 1 minute after the first, third, fifth and seventh breath-hold. Results: Average duration of the seven breath-holds did not differ between conditions (25.3 s ±1.4 s, p=0.231). The apnea-induced bradycardia was stronger with FIA (from 134 ±4 to 85 ±3 bpm) than DRA (from 134 ±4 to 100 ±5 bpm, p < 0.001). mTOI decreased significantly from 69.9 ±0.9% to 63.0 ±1.3% (p<0.001) which is reflected in a steady decrease in m[O2Hb] (p<0.001) and concomitant increase in m[HHb] (p=0.001). However, this was similar in both conditions conditions (0.121